(La0.2Ce0.2Nd0.2Sm0.2Eu0.2)PO4: A high-entropy rare-earth phosphate monazite ceramic with low thermal conductivity and good compatibility with Al2O3. Issue 12 (December 2019) - Zhao, Zifan; Chen, Heng; Xiang, Huimin; Dai, Fu-Zhi; Wang, Xiaohui; Peng, Zhijian; Zhou, Yanchun
Abstract: Low thermal conductivity, matched thermal expansion coefficient and good compatibility are general requirements for the environmental/thermal barrier coatings (EBCs/TBCs) and interphases for Al2 O3f /Al2 O3 composites. In this work, a novel high-entropy (HE) rare-earth phosphate monazite ceramic (La0.2 Ce0.2 Nd0.2 Sm0.2 Eu0.2 )PO4 is designed and successfully synthesized. This new type of HE rare-earth phosphate monazite exhibits good chemical compatibility with Al2 O3, without reaction with Al2 O3 as high as 1600 °C in air. Moreover, the thermal expansion coefficient (TEC) of HE (La0.2 Ce0.2 Nd0.2 Sm0.2 Eu0.2 )PO4 (8.9 × 10 -6 /°C at 300–1000 °C) is close to that of Al2 O3 . The thermal conductivity of HE (La0.2 Ce0.2 Nd0.2 Sm0.2 Eu0.2 )PO4 at room temperature is as low as 2.08 W·m -1 ·K -1, which is about 42% lower than that of LaPO4 . Good chemical compatibility, close TEC to that of Al2 O3, and low thermal conductivity indicate that HE (La0.2 Ce0.2 Nd0.2 Sm0.2 Eu0.2 )PO4 is suitable as a candidate EBC/TBC material and an interphase for Al2 O3f /Al2 O3 composites.